Професійне самовиховання особистості студента як чинник формування успішного фахівця - Грень, Лариса Миколаївна (НТУ "ХПI", 2010)
In the article the necessity of forming of successful specialist is grounded for higher educational establishment. Essence and features of professional self-education opens up. A difference is certain between a self-education and a self-intelligent. Expedience of the use is well-proven I am conception in the professional self-education of students.
Keywords: самовиховання; саморозвиток; концепція